2022
DOI: 10.3389/fitd.2022.868645
|View full text |Cite
|
Sign up to set email alerts
|

Fetotoxicity and Subacute Toxicity of Some Plants Involved in the Treatment of Infectious Diarrhea in Benin

Abstract: This study aimed to provide data on the subacute toxicity and fetotoxicity of aqueous and hydroethanolic extracts of Daniellia oliveri (Rolfe) Hutch. & Dalziel, Anacardium occidentale L., Diospyros mespiliformis Hochst. ex A. DC., Khaya senegalensis (Desv.) A. Juss., Ocimum gratissimum L., Vernonia amygdalina Delile, Pterocarpus erinaceus Poir., and Manihot esculenta Crantz used in the treatment of diarrheal diseases in Benin. For subacute toxicity, each male and female Wistar rat received by esophagea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Nine male Wistar rats, aged 12 weeks and weighing an average of 152.44 ± 3.68 g, were housed in wire mesh cages measuring 50 × 30 × 20 cm 3 upon receipt. Tey were kept in accordance with the experimental conditions outlined by the OECD (Organization for Economic Cooperation and Development) Guideline-423, adopted on December 23, 2001, as per previous studies [17]. Te temperature of the room was maintained at 25 degrees Celsius, and artifcial lighting was provided in alternating cycles of 12 hours of light and 12 hours of darkness.…”
Section: Acute Toxicity Studymentioning
confidence: 99%
“…Nine male Wistar rats, aged 12 weeks and weighing an average of 152.44 ± 3.68 g, were housed in wire mesh cages measuring 50 × 30 × 20 cm 3 upon receipt. Tey were kept in accordance with the experimental conditions outlined by the OECD (Organization for Economic Cooperation and Development) Guideline-423, adopted on December 23, 2001, as per previous studies [17]. Te temperature of the room was maintained at 25 degrees Celsius, and artifcial lighting was provided in alternating cycles of 12 hours of light and 12 hours of darkness.…”
Section: Acute Toxicity Studymentioning
confidence: 99%
“…The antioxidant, hepato-protective and antimicrobial activities of A. cordifolia leaves are an asset for the protection of certain organs such as the pancreas, liver, kidneys, heart and spleen, which are subject to tissue damage in an environment of chronic hyperglycemia [52,53]. Also, the work of Hounsa et al [54] showed that O. gratissimum extracts are not toxic by the oral route, as their administration to mice produced no mortality or signs of toxicity. Hounsa et al also revealed that administration of these extracts caused no significant weight variation (P>0.05) in treated animals compared with corresponding controls.…”
Section: Discussionmentioning
confidence: 99%